The An Integrated Pre-Pressure Prediction Approach: Open-Up Opportunity for the Untouchable Pools by Drilling Through Highly Depleted Zone, Semberah Field, Indonesia - , U. Jauhari ([Yogyakarta] : Departemnts of Geological Engineering Faculty of E, 2009)
Semberah field is one of main oil and gas producing fields operated by Vico Indonesia in East Kalimantan, Indonesia. Production of gas and oil has been concentrated mostly from shallowlevel reservoirs (C-I intervals). Meanwhile, deep reservoirs (J Interval) are rarely penetrated. After production for almost 20 years, the shallow and high-perm intervals are currently very low pressure. Significant remaining reserves are still underground residing in the deep and low-perm reservoirs. Accessing the reserves is a highly challenging work today. Early TD in drilling has frequently to be set early because of severe loss circulation before reaching the main deep targets. This paper illustrates an integrated pore pressure prediction carried out to plan drilling and completion of a new well (Semberah-S6) to access deep target zones of J070AB and J075A by safely drilling through highly-depleted IOS2Asandstone. The analysis integrates well logs and pressure data including LOT, RFT, MDT, BHP and historicalmatch derived estimated pressures. This work is a close integration of geoscientists, reservoir engineers, operation geologists and drilling engmeers. The study results in a prediction that the new well of Semberah-S6 will pass through variously depleted zones of 2.6 to 5.S ppg at shallow level before entering IOS2Asandstone. Within IOS2A sandstone, an extreme low pressure of 400 psi/0.S7 ppg will be experienced. Below this sandstone, the new well will penetrate overpressure interval. The study recommends that: I) to set 9-5/S&quot